Ethical Leadership, Psychological Contract, dan Work-Family Conflict: Determinan Loyalitas Perawat di Era Pandemi - Efrial, Annisa Syafira (Jurnal Manajemen dan Usahawan Indonesia, 2025)
Nurses are the frontline of healthcare services and have faced increasing work pressure during the COVID-19 pandemic. In this context, nurse loyalty becomes a crucial factor for the sustainability of healthcare organizations. This study aims to analyze the influence of ethical leadership on employee loyalty by examining the mediating roles of psychological contract and work-family conflict. A total of 145 nurses participated in this study. Data were analyzed using a quantitative approach through Structural Equation Modeling (SEM) with the assistance of Lisrel 8.80. The findings reveal that ethical leadership has a positive effect on both employee loyalty and psychological contract. However, psychological contract and work-family conflict were not found to mediate the relationship between ethical leadership and employee loyalty. These results highlight the importance of ethical leadership in fostering nurse loyalty, although the tested mediating variables did not significantly contribute to the relationship.